Contingent employment, health and sickness absence - Virtanen, Marianna; Kivimäki, Mika; Elovainio, Marko; Vahtera, Jussi; Cooper, CaryL (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study explored the health and sickness absences of contingent employees. ' ' METHODS ': 'Analyses of self-reported health and recorded spells of sickness absence were based on a cohort of 5650 employees (674 men, 4976 women) in 10 Finnish hospitals. ' ' RESULTS ': 'After adjustment for demographic and work-related characteristics, contingent employees had a better self-rated health status [odds ratio 0.76, 95% confidence interval (95% CI) 0.62-0.94 of poor or average health status]. There were no differences in the prevalence of diagnosed chronic diseases and minor psychiatric morbidity between the groups. After adjustment for self-rated health and confounding, female, but not male, contingent employees had a lower rate of self-certified (1-3 days) sickness absences than permanent employees (rate ratio 0.90, 95% CI 0.85-0.95). Contingent employees, irrespective of gender, had a 0.77 (95% CI 0.71-0.84) times lower rate of medically certified (>3 days) sickness absence than permanent employees. Poor self-rated health status, reported diagnosed chronic diseases, and minor psychiatric morbidity were associated with medically certified absences to a less extent among contingent employees than among permanent employees. ' ' CONCLUSIONS ': 'These findings suggest better self-rated health and a lower sickness absence rate for contingent employees than for permanent employees. The difference in sickness absence between the groups seems not only to be associated with actual differences in health, but also with different thresholds of taking sick leave or working while ill.
Keywords: absenteeism; contingent employment; employment status; health; health psychology; hospital staff; job insecurity; mental health; perceived health; sickness absence; temporary employment